Datalogging Findings in Adult Cochlear Implant Recipients Who Never Developed Intelligible Speech - Loureiro, Manuel; Bradley, Jane; Clemesha, Jennifer; Mehta, Nishchay (Journal of International Advanced Otology, 2024)
BACKGROUND: The aim was to evaluate the usage patterns of adult cochlear implant recipients with a history of pre-lingual or peri-lingual acquired deafness and poor speech intelligibility. METHODS: A retrospective chart review of all patients meeting inclusion criteria within the patient cohort of the auditory implant centre of the University College London Hospitals was conducted. Outcome measurements included sound processor daily usage and speech perception scores postimplantation. RESULTS: Fifty-nine adults met the inclusion criteria. Daily usage was found to be 8.7 hours per day on average (range: 7.9-9.7 hours) at 4.6 years postimplantation. Five recipients became nonusers (8.5%). Average usage of 11.0 daily hours at 3 months postimplantation was a significant predictor of implant usage at 4.6 years. On average, Bamford–Kowal–Bench sentence scores did not improve significantly by 1 year postimplantation. Neither the preimplantation speech intelligibility rating nor the Bamford–Kowal–Bench sentence scores were significantly correlated with postoperative usage data. CONCLUSION: Despite non-significant improvements to speech perception scores in this patient cohort, pre-lingual and peri-lingual cochlear implant recipients are consistent users of their devices, with an average daily use of 11.0 hours at 3 months postimplantation and 8.7 hours at 4.6 years. Consistent users at 3-months postimplant are likely to continue being consistent users at 4.6 years after implantation. Understanding likely usage rates is an important consideration for patients and clinicians in the shared decision-making process about whether to undergo cochlear implantation. Further research is needed to understand why this group of patients, who receive no benefit from speech intelligibility, choose to wear their processors so consistently. Cite this article as: Loureiro M, Bradley J, Clemesha J, Mehta N. Datalogging findings in adult cochlear implant recipients who never developed intelligible speech. J Int Adv Otol. 2024;20(2):113-118.